Efficacy and safety of dacron patch in surgical treatment of congenital disease by echocardiography. Issue 12 (December 2020) - Deng, Mingbin; Yang, Qi
Abstract: To evaluate the efficacy and safety of a new domestic dacron patch in the surgical treatment of congenital heart disease (CHD) with infective endocarditis (IE), a clinical controlled trial is conducted. 48 patients with CHD complicated with IE are selected and randomly divided into two groups. 26 patients in the experimental group are treated with a new domestic dacron patch, while 22 patients in the control group are treated with an imported cardiac polyester patch. By echocardiography, collecting chest X-ray, echocardiography and laboratory examination before and after operation, the residual shunt, cardiac function, liver function, renal function, coagulation function and other related indicators are observed after operation in the two groups, and the therapeutic effect and safety of the new dacron patch are evaluated. The results showed that there is no significant difference in C/T (cardiothoracic ratio), LAD (Left atrial diameter), LVSD (left ventricular end systolic diameter) and LVDD (left ventricular end diastolic diameter) between the two groups before operation, before discharge and 1, 3 and 6 months after discharge (P > 0.05). The C/T, LAD and LVDD of the two groups decrease 6 months after operation, and the size of atrioventricle decreases significantly. There is a decreasing trend in the experimental group compared with the control group, but there is no significant difference (P > 0.05). There are no significant differences in cardiac function classification, echocardiography, electrocardiogram, patch performance evaluation and blood compatibility between the two groups before operation and 6 months after discharge. Conclusion: The new domestic dacron patch has good clinical efficacy and safety.